Characteristics of Microplastic in Selected Marine Sponges from Pasir Putih Situbondo, East Java, Indonesia - Fauziah, Natasya Febriani; Muzaki, Farid Kamal; Fajrinia, Naurah Rizki; Aunurohim, Aunurohim; Saptarini, Dian (HAYATI Journal of Biosciences, 2025)
Microplastics (MPs) are global concern due to their presence in various ecosystems and their tendency to have a negative impact on organisms. MPs are plastic fragments with a small size ranging from >1 μm to